Desenvolvimento de sistemas multifuncionais baseados em híbridos orgânico-inorgânicos dopados - Santos, Fábio Cesar dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Environmentally compliant organic-inorganic hybrid coatings for efficient corrosion protection of metallic surfaces are alternatives to the current methods based on chromate passivation. In this context hybrids coatings were prepared using the sol-gel process from the radical polymerization of methyl methacrylate (MMA) and 3-(Trimethoxysilyl)propyl methacrylate (MPTS) followed by the step of acidic hydrolysis and polycondensation of the silanes tetraethoxysilane (TEOS) and 3-(Trimethoxysilyl)propyl methacrylate (MPTS). To investigate the effectiveness of the hydrolysis/polycondensation process and the resulting structural properties, coatings were prepared with different ethanol to water proportions (0 < Ethanol/H2O < 1) for constant organic to inorganic phase ratio (MMA/TEOS = 4). The structural properties of ~2 μm thick films, deposited onto carbon steel substrates by dip-coating, were correlated with their anti corrosion efficiency. Nuclear magnetic resonance, X-ray photoelectron spectroscopy, thermogravimetry and nanoscratch test were used to study the structural properties and adhesion on steel. Electrochemical impedance spectroscopy and potentiodynamic polarization curves were carried out to evaluate the corrosion resistance of the coated samples after long-term exposure in standard saline (3,5%) and saline/acid (pH 1)environments. The results of structural analysis showed that in a intermediate Ethanol/H2O range the enhanced reactivity of alcoxy groups during the hydrolysis process results in a high connectivity (>83%) of the hybrid network, which harbors efficiently the completely polymerized organic phase and thus provides a dense composite structure with high thermal stability. The nanoscratch test showed that the coatings have a very good adhesion to steel and low surface roughness. The electrochemical measurements showed that the sample with ethanol to H2O ratio of 0.2, has the highest corrosion resistance of up to 10 GΩ...

Revestimentos ambientalmente compatíveis híbridos orgânico-inorgânicos para proteção contra a corrosão de superfícies metálicas são alternativas aos métodos baseados em passivação que utilizam cromatos. Neste contexto, revestimentos híbridos foram preparados utilizando o processo sol-gel a partir da polimerização radicalar entre o metacrilato de metila (MMA) e o 3- metacriloxipropriltrimetoxisilano (MPTS) seguido pela etapa de hidrólise e policondensação ácida dos silanos tetraetoxisilano (TEOS) e 3- metacriloxipropriltrimetoxisilano (MPTS).Para investigar a efetividade das reações de hidrólise/condensação e propriedades estruturais resultantes, revestimentos foram preparados com diferentes proporções Etanol para água (0 < Etanol/ H2O < 1) para uma razão orgânico/inorgânico constante (MMA/TEOS = 4). As propriedades estruturais dos revestimentos com espessura de ~2 μmdepositados sobre substratos de aço carbono por dip-coating, foram correlacionadas com sua eficiência anticorrosiva. Ressonância magnética nuclear, espectroscopia de fotoelétrons induzidos por raios-X, termogravimetria e testes de nanoscratch foram utilizados para estudar as propriedades estruturais e adesão filme/substrato. Espectroscopia de impedância eletroquímica e curvas de polarização foram conduzidos para elucidar a resistência contra a corrosão das amostras revestidas após longos períodos de exposição ao meio salino (NaCl 3,5%) e salino/ácido (pH 1). Os resultados das análises estruturais mostraram que para uma razão intermediária Etanol/H2O, a reatividade dos grupos silanóis durante as reações de hidrólise e condensação resulta em uma alta conectividade da rede inorgânica (> 83%) da rede híbrida, que abriga eficientemente a fase orgânica e assim fornece uma densa estrutura compósita com alta estabilidade térmica. Os teste de nanoscratch mostraram que os revestimentos possuem ótima adesão ao aço e baixa rugosidade.
Keywords: Físico-química; Processo sol-gel; Corrosão e anticorrosivos; Revestimentos protetores; Sol-gel process